1965
DOI: 10.1002/app.1965.070090722
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization of amorphous cellulose

Abstract: SynopsisRecrystallization of amorphous cellulose prepared by saponification of cellulose triacetate in an non-aqueous medium was found to occur only at very high relative humidities, i.e., near 100%. At lower relative humidities the amount of recrystallization occurring was slight though significant. Correspondingly, the accessibility decreased from 90% (for amorphous cellulose) to a minimum of 79%, the same as that for cellulose 11. The mechanism of recrystallization is discussed in terms of the surface tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…Noncrystalline cellulose in an aqueous solvent can crystallize into cellulose II during removal of water; therefore, it is important to establish that the cellulose II pattern observed is not a consequence of drying (22). Water-washed never-dried as well as organicsolvent-exchanged in vitro product also gave a cellulose II pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncrystalline cellulose in an aqueous solvent can crystallize into cellulose II during removal of water; therefore, it is important to establish that the cellulose II pattern observed is not a consequence of drying (22). Water-washed never-dried as well as organicsolvent-exchanged in vitro product also gave a cellulose II pattern.…”
Section: Discussionmentioning
confidence: 99%
“…USA 84 (1987) 6987 washed with water three times, and packed without drying directly into a glass capillary tube. (B) Never-dried in vitro product was subjected to organic solvent exchange by washing three times with methanol followed by three washes with n-pentane (22). The organic solvent-exchanged in vitro product suspended in n-pentane was then dried over P205 in a vacuum desiccator.…”
mentioning
confidence: 99%
“…It is likely that the opportunities for formation of crystallites in the zone of adhesion between adjacent fibers is limited by the presence of materials other than pure cellulose at the surfaces of the adjacent fibers, and also the stringent requirements for alignment in order for adjacent crystallites to "heal together," forming a single unit (Wool 2008). Much more extensive formation of crystallites might be possible if a fully amorphous cellulose, which has to be carefully prepared in the laboratory, were placed in water (Wadehra and Manley 1965). Work by Kontturi et al (2011) showed, however, that certain amorphous cellulose materials can resist conversion to a crystalline form even when they are exposed to water.…”
Section: Self-assembly Microfibril Coalescencementioning
confidence: 99%
“…The amorphous films revealed an interesting behavior in that they did not undergo H/D exchange to a full extent. Although Wadehra [39] and Jeffries [40] had already reported that the materials could probably recrystallize upon D 2 O vapor exposure, Kondo and colleagues argued differently. One of their arguments was that, upon recrystallization, the H/D exchange rate changed significantly, as well as the absorption band of the νOH vibrations.…”
Section: Scattering and Diffractionmentioning
confidence: 95%